Pengaruh Komposisi Polipropilena Terhadap Kekuatan Asphalt Concrete Wearing Coarse dengan Pengujian Marshall Test - Budi Florianta Tarigan; Nurdiana Nurdiana (Universitas Quality, 2018)
Research on the effect of adding to the strength polypropylene plastic material mix Asphalt Concrete Wearing Coarse. Before the making of the specimen, do Design and mixed (mix design) that includes planning, determination and measurement of asphalt composition of each fraction better each aggregate asphalt, polypropylene and filler. After the job mix, made with a sample weight of 1200 g, and by varying the composition of polypropylene 2%, 3%, and 5% of the aggregate weight of stone dust. Methods of testing is done by using the Marshall test ie based on the results of Stability, Flow and Marshal Quontent. The results showed that the value of stability, flow and Marshal Quontent has met the specifications of Highways 2010 Revision 3